Type III secretion as a generalizable strategy for the production of full‐length biopolymer‐forming proteins. Issue 11 (30th June 2015) - Azam, Anum; Li, Cheng; Metcalf, Kevin J.; Tullman‐Ercek, Danielle
ABSTRACT: Biopolymer‐forming proteins are integral in the development of customizable biomaterials, but recombinant expression of these proteins is challenging. In particular, biopolymer‐forming proteins have repetitive, glycine‐rich domains and, like many heterologously expressed proteins, are prone to incomplete translation, aggregation, and proteolytic degradation in the production host. This necessitates tailored purification processes to isolate each full‐length protein of interest from the truncated forms as well as other contaminating proteins; owing to the repetitive nature of these proteins, the truncated polypeptides can have very similar chemistry to the full‐length form and are difficult to separate from the full‐length protein. We hypothesized that bacterial expression and secretion would be a promising alternative option for biomaterials‐forming proteins, simplifying isolation of the full‐length target protein. By using a selective secretion system, truncated forms of the protein are not secreted and thus are not found in the culture harvest. We show that a synthetically upregulated type III secretion system leads to a general increase in secretion titer for each protein that we tested. Moreover, we observe a substantial enhancement in the homogeneity of full‐length forms of pro‐resilin, tropo‐elastin crosslinking domains, and silk proteins produced in this manner, as compared with proteins purified from the cytosol. Secretion via the type III apparatus limits co‐purification of truncated forms of the target protein and increases protein purity without extensive purification steps. Demonstrating the utility of such a system, we introduce several modifications to resilin‐based peptides and use an un‐optimized, single‐column process to purify these proteins. The resulting materials are of sufficiently high quantity and yield for the production of antimicrobial hydrogels with highly reproducible rheological properties. The ease of this process and its applicability to an array of engineered biomaterial‐forming peptides lend support for the application of bacterial expression and secretion for other proteins that are traditionally difficult to express and isolate from the bacterial cytoplasm. Biotechnol. Bioeng. 2016;113: 2313–2320. © 2015 Wiley Periodicals, Inc. Abstract : The type III secretion system (T3SS) is a protein machine used by pathogenic bacteria to deliver toxic proteins into eukaryotic cells. In this work, Azam and coworkers engineered bacteria that have a T3SS that secretes highly pure, customizable biopolymer proteins. The proteins can then be cross‐linked with polyethylene glycol to make mechanically stable hydrogels that kill bacteria, but permit mammalian cell growth.